Acute‐onset delirium in intensive care COVID patients: association of imperfect brain repair with foodborne micro‐pollutants. (26th March 2021) - Schneider, Francis; Agin, Arnaud; Baldacini, Mathieu; Maurer, Loïc; Schenck, Maleka; Alemann, Mathieu; Solis, Morgane; Helms, Julie; Villette, Claire; Artzner, Thierry; Kremer, Stéphane; Heintz, Dimitri
Abstract: Background and purpose: COVID‐19 affects the brain in various ways, amongst which delirium is worrying. An assessment was made of whether a specific, long‐lasting, COVID‐19‐related brain injury develops in acute respiratory distress syndrome patients after life‐saving re‐oxygenation. Methods: Ten COVID+ patients (COVID+) with unusual delirium associated with neuroimaging suggestive of diffuse brain injury and seven controls with non‐COVID encephalopathy were studied. The assessment took place when the intractable delirium started at weaning off ventilation support. Brain magnetic resonance imaging (MRI) was performed followed by standard cerebrospinal fluid (CSF) analyses and assessment of CSF erythropoietin concentrations (as a marker for the assessment of tissue repair), and of non‐targeted CSF metabolomics using liquid chromatography high resolution mass spectrometry. Results: Patients were similar as regards severity scores, but COVID+ were hospitalized longer (25 [11.75; 25] vs. 9 [4.5; 12.5] days, p  = 0.03). On admission, but not at MRI and lumbar puncture performance, COVID+ were more hypoxic ( p  = 0.002). On MRI, there were leptomeningeal enhancement and diffuse white matter haemorrhages only in COVID+. In the latter, CSF erythropoietin concentration was lower (1.73 [1.6; 2.06] vs. 3.04 [2.9; 3.91] mIU/ml, p  = 0.01), and CSF metabolomics indicated (a) increased compounds such as foodborne molecules (sesquiterpenes), molecules from industrialized beverages and micro‐pollutants (diethanolamine); and (b) decreased molecules such as incomplete breakdown products of protein catabolism and foodborne molecules (glabridin). At 3‐month discharge, fatigue, anxiety and depression as well as MRI lesions persisted in COVID+. Conclusions: Some COVID+ are at risk of a specific delirium. Imperfect brain repair after re‐oxygenation and lifestyle factors might influence long‐lasting brain injuries in a context of foodborne micro‐pollutants. Abstract : This explorative cohort study suggests that life‐saving re‐oxygenation of COVID+ patients is possibly followed by an incomplete brain repair as indicated by magnetic resonance imaging and low cerebrospinal fluid erythropoietin (CSF EPO) concentrations. In addition, non‐targeted metabolomics analysis identified the presence of many perturbed metabolites during COVID‐induced delirium, including biomarkers for the consumption of specific food and intermediate factors that have tangible impact on inflammatory pathways.